La tragedia lopesca en los años 1620-1630: ¿de un paradigma a otro? - Florence d’Artois (Mélanges de la Casa de Velázquez)
After first recalling that there is a coherent tragic praxis in the work of Lope post-1590, this article examines the ways in which that praxis evolved in the years 1620-1630, with a view to determining the scope of the phenomenon, and above all the possible reasons for it. Was this evolution a radical one? What is the chronology? Which of the elements that we propose to call a «tragic pattern» does it affect? And finally, to what extent does this evolution relate to a context that critics often consider decisive (evolution of audiences, competition from a new generation of playwrights, changes of reign, penetration by Aristotelian poetics)?